# Warm up #9 ch 6: Solve for x 1 (x – 3)(x + 5) = 0 2 (2x – 4)x = 0 3 x 2 + 4x + 3 = 0 4 X 2 + 6x + 9 = 0 5 9x 2 – 16 = 0 x = 3 or -5 x = 0 or 2 x = -1 or.

## Presentation on theme: "Warm up #9 ch 6: Solve for x 1 (x – 3)(x + 5) = 0 2 (2x – 4)x = 0 3 x 2 + 4x + 3 = 0 4 X 2 + 6x + 9 = 0 5 9x 2 – 16 = 0 x = 3 or -5 x = 0 or 2 x = -1 or."— Presentation transcript:

Warm up #9 ch 6: Solve for x 1 (x – 3)(x + 5) = 0 2 (2x – 4)x = 0 3 x 2 + 4x + 3 = 0 4 X 2 + 6x + 9 = 0 5 9x 2 – 16 = 0 x = 3 or -5 x = 0 or 2 x = -1 or -3 x = -3

6.9 Using Equations that Factor Goal: Solve problems by writing and solving equation

Translate to an equation and solve. 1. The product of two consecutive positive even integers is 48. Find the two integers. Let n = first even integer (n + 2) = 2nd even integer n(n + 2) = 48 n 2 + 2n = 48 n 2 + 2n - 48= 0 (n + 8)(n – 6)= 0 n = -8, 6 X 6 and 8

Translate to an equation and solve. 1. The product of two consecutive positive odd integers is 143. Find the two integers. Let n = first odd integer (n + 2) = 2nd odd integer n(n + 2) = 143 n 2 + 2n = 143 n 2 + 2n - 143= 0 (n - 11)(n + 13)= 0 n = -13, 11 X 11 and 13

2. One side of a rectangle is 4 in. longer than the other. If the sides are each increased by 2 in., the area of the new rectangle is 60 in 2. How long are the sides of the original rectangle? (x+2)(x +6) = 60 x 2 + 8x + 12 = 60 x 2 + 8x - 48= 0 (x + 12)(x – 4)= 0 x = -12, 4 X 4 and 8 X X+4 X+2 X+4+2 A = 60 in 2

The sum of the squares of two consecutive even integers is 244. Find the two integers. 10 and 12. Also, -12 and -10 Let n² = first consecutive square Let (n+2)² = the 2 nd consecutive square (n)² +(n+2) ²=244 n² +n² +4n +4 =244 2n² +4n +4 =244 2(n²+2n +2) =244 n² +2n +2 =122 n²+2n -120 =0 (n-10) (n+12) =0 n-10 =0 or n +12 =0 If n=10 then n+2 = 12 If n =-12 then n+2 =-10

Page 294, 1 - 20

7,8 and –7, -8

Assignment: Page 294 (2-20) even

Page 294, 1 - 20 13,14 and –13, -14

Page 294, 1 - 20

Download ppt "Warm up #9 ch 6: Solve for x 1 (x – 3)(x + 5) = 0 2 (2x – 4)x = 0 3 x 2 + 4x + 3 = 0 4 X 2 + 6x + 9 = 0 5 9x 2 – 16 = 0 x = 3 or -5 x = 0 or 2 x = -1 or."

Similar presentations